THERMAL EQUATION OF STATE OF FE3S AND IMPLICATIONS FOR SULFUR IN EARTH'S CORE - Seagle C.T.; Heinz D.L.; Campbell A.J.; Shen G.; Prakapenka V.B. (My University, 2006)
Iron (Fe) and coexisting Fe3S were studied simultaneously using synchrotron X-ray diffraction and a laser-heated diamond anvil cell (DAC). The thermal equation of state (EOS) of Fe3S was investigated up to pressures of 80 GPa and temperatures of 2500 K. Fitting a third-order Birch-Murnaghan EOS to the room temperature data yielded bulk modulus K0 = 156(7) GPa (values in parentheses are standard deviation) and pressure derivative K′0 = 3.8(3) calibrated against NaCl in the B2 structure. The room temperature data were also calibrated against the EOS of hcp-Fe for comparison and aid in the determination of the thermal pressure contribution of Fe3S. This fit yielded bulk modulus K0 = 113(9) GPa and pressure derivative K′0 = 5.2(6). The thermal pressure contribution of Fe3S was assumed to be of the form ΔPthermal = αKTΔT, where αKT is constant. The best fit to the data yielded αKT = 0.011(2) GPa K-1. Iron and Fe3S coexisted in the high-pressure, high-temperature experiments, and a density relationship between Fe and Fe3S was found to be linear and independent of temperature. Extrapolation of the data to the core-mantle boundary (CMB), using an assumed temperature of 3500 K at the CMB, a 2% volume change associated with melting, and applying a small adjustment to account for the nickel content of the core indicates that 14.7(11) wt% sulfur is adequate to resolve the density deficit of the outer core. Copyright 2006 by the American Geophysical Union.